(untitled) (Economics and region, 2024)
The article identifies the main advantages of using digital technologies to increase business activity. It was proved that in today’s conditions, digitalization of business is a prerequisite for its competitiveness in the market. The authors substantiate the necessity of introducing new technologies into business processes to improve production efficiency, accelerate asset turnover and minimize costs. The article details the components of the concept of sustainable development, the main idea of which is strategic actions aimed at reducing the negative impact of companies on the environment and increasing its positive impact on social development, rather than just maximizing profits. This idea stems from the realization that business cannot operate in isolation from the environment and society. The concept of sustainable development in doing business has gained wide popularity all over the world. In Ukraine, the main industries that are first ready to accept digital transformations are those where there is high competition, rather management decisions are made and strict conditions for entering the market, for example, the confectionery industry. The level of business activity of confectionery enterprises in Ukraine was determined, the competitive environment of the industry was characterized, and directions for improving business activity through the introduction of innovative digital technologies and the implementation of the concept of sustainable development were proposed. It was proved that the introduction of the concept of sustainable development along with the digitalization of business processes creates a synergistic effect to increase business activity.